Immature stages and redescription of Lejops barbiellinii (Ceresa) (Diptera, Syrphidae) found in bromeliads in Brazil - Morales, Mírian Nunes; Marinoni, Luciane (Zootaxa, 2008)
A new combination is proposed: Habromyia barbiellinii (Hull 1946) = Lejops barbiellinii (Ceresa 1934). Third-stage larvae and puparia of Lejops barbiellinii are described and the adult male redescribed. The larvae were found in phytotelmata of terrestrial Bromeliaceae in Parque Estadual do Rio da Onça, Matinhos, Paraná, Brazil.